Front End Engineering (FEE) Application in Baronia Field - RAMLI, AMIRA ALYA SYAHIRAH; Zainun , Noor Yasmin (Recent Trends in Civil Engineering and Built Environment, 2022)
Front End Engineering (FEE) is simply refer as early project planning phase. It can also be known as Pre Project Planning (PPP), Front End Loading (FEL), Front End Planning (FEP), Front End Engineering Design (FEED), Front End Development (FED) and Front End Decision Making (FEDM). The purpose for FEE application in a project is to identify the risks in the early stage and propose solutions to ensure a smooth progress of the project. Henceforth, this study is conducted to identify the FEE application and establish effectiveness of the application in Baronia Field which located in Miri, Sarawak. From this study, the data for project scheduling and cost are collected from the project’s person in charge (PIC). Therefore, from the project schedule the project completed as planned in 2020. In addition, the cost for the project does not overrun from the estimate cost. From this, it shows that the project performance is execute smoothly. Therefore, it is concluded that FEE application is effective on Baronia Field.